Patient experience, satisfaction, and adherence: Mediating roles of communication and outcome quality among geriatrics - Stepvia, Stepvia; Silimalar, Juan AG.; Jayanagara, Oscar (Narra J, 2026)
Treatment adherence among geriatric population remains a challenge due to multimorbidity, polypharmacy, and communication barriers. Although patient experience and satisfaction are major predictors of treatment adherence, the mediating pathways involving communication and perceived outcome quality, patients' perceptions of the effectiveness of treatment, including symptom relief, functional improvement, and overall quality of life, have not been explored, particularly in healthcare systems of developing countries. This study aimed to examine the effects of patient experience and satisfaction on treatment adherence, with service communication and perceived outcome quality serving as mediating variables. A cross-sectional study was conducted at the Geriatric Outpatient Clinic of RSUPN Dr. Cipto Mangunkusumo Hospital between June and September 2025. A total of 221 geriatric patients aged ≥60 years completed validated questionnaires on five constructs using six-point Likert scales. Data were analyzed using Partial Least Squares Structural Equation Modeling, with model validity and reliability confirmed through average variance extracted, composite reliability, and variance inflation factor indicators. Patient experience (β=0.260, p<0.001) and satisfaction (β=0.158, p<0.001) significantly improved adherence. Service communication (β=0.352, p<0.001) and outcome quality (β=0.249, p<0.001) partially mediated these effects, explaining 74% of adherence variance (R²=0.740). Communication showed stronger mediation, underscoring the importance of empathy, clarity, responsiveness, and shared decision-making in fostering adherence. Enhancing patient experience and satisfaction through effective communication, collaborative care, and perceived positive outcomes may strengthen adherence and optimize service quality in geriatrics, particularly in resource-limited health systems.